PROYEKSI KETAHANAN PANGAN PROVINSI NUSA TENGGARA TIMUR TAHUN 2015-2045 DITINJAU DARI KETERSEDIAAN, KEBUTUHAN, DAN PERSEDIAAN BERAS - Alvin Anindita Katon Sumunar; Satrio Budiman (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2021)
Regional independence in fulfilling food demand is expected to increase agriculture products, both in the diversification aspect and food management. This paper aims to determine how food development strategies are, especially rice, in this climate change situation nowadays. Food planning in East Nusa Tenggara Province is done by rice availability, demand, and supply in 2015–2045. According to scenarios, these projections describe that rice supply in East Nusa Tenggara Province is surplus while the harvest area is increasing and deficit while the harvest area is decreasing. Therefore, food planning is needed regarding food availability to remain food supply in the latter days. Food demand planning can be used as a policy basis to make food supply still stable, increase the welfare of farmers and society, and even increase both East Nusa Tenggara Province’s GDRP and Indonesia’s GDP.